Water molecules role and impact on recombination processes in lithium sulfate monohydrate - Кoketay, Т.А.; Кim, L.М.; Nurpeissov, R.A.; Tagaeva, B.S. (Publishing House of the KarSU named after E.A.Buketov, 2013)
Curves of a thermal luminescence in Li2SO4H2O are studied. For an explanation of the received results quantum and chemical calculations are carried out. It is shown that radiolysis products molecules of water lead to disintegration of sulphatic anions. On the other hand they "switch off" defects of a sulphatic subsystem from recombination processes.
Keywords: thermal luminescence; lithium sulfate monohydrate; "switch off" defects; recombination processes